2019
DOI: 10.2220/biomedres.40.235
|View full text |Cite
|
Sign up to set email alerts
|

T-cell activation-inhibitory assay: a proposed novel method for screening caloric restriction mimetics

Abstract: Caloric restriction (CR) is a major contributor to good health and longevity. CR mimetics (CRMs) are a group of plant-derived compounds capable of inducing the benefits of CR. Since a longevity gene, SIRT1, inhibits T-cell activation and SIRT1 loss results in increased T-cell activation, we hypothesized that compounds capable of activating SIRT1 signaling can inhibit T-cell activation and function as CRMs. Thus we propose, in the present study, the application of a T-cell activation-inhibitory assay to screen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…32 We have previously reported a practical approach for screening healthy compounds with metabolism-improving actions. 33 Using this screening method, we have identified phytochemicals, including cynandione A 34,35 and N-caffeoyltryptophan, 36 with beneficial effects on metabolism. In a preliminary experiment, we applied this screening method for DR and found a candidate compound, tipepidine (TP; chemically 3-[di-2-thienylmethylene]-1-methylpiperid ine) (Figure 1A), a non-narcotic antitussive drug, which has been used for more than 60 years since its approval in Japan in 1959, and its safety for use in all age groups is well established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 We have previously reported a practical approach for screening healthy compounds with metabolism-improving actions. 33 Using this screening method, we have identified phytochemicals, including cynandione A 34,35 and N-caffeoyltryptophan, 36 with beneficial effects on metabolism. In a preliminary experiment, we applied this screening method for DR and found a candidate compound, tipepidine (TP; chemically 3-[di-2-thienylmethylene]-1-methylpiperid ine) (Figure 1A), a non-narcotic antitussive drug, which has been used for more than 60 years since its approval in Japan in 1959, and its safety for use in all age groups is well established.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported a practical approach for screening healthy compounds with metabolism‐improving actions 33 . Using this screening method, we have identified phytochemicals, including cynandione A 34,35 and N ‐caffeoyltryptophan, 36 with beneficial effects on metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Kaneko and Nagashima 6) proposed the idea of drug repositioning based on clinical evidence from a voluntary reporting database, such as the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS). Yamamoto et al 7) reported that nafamostat mesylate, a drug used for disseminated intravascular coagulation (DIC), inhibits severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in vitro, suggesting the possibility of repositioning this drug to treat coronavirus pneumonia disease . In this report, we propose another approach of drug repositioning using an experimental assay system.…”
Section: Introductionmentioning
confidence: 99%